Traumatic facial arteriovenous fistula: a rare case report and literature review - Hongwei Gao; Donglin Zhou; You Zhou; Xuechao Wu; Jing Wang; Qing Wang (International Journal of Emergency Medicine)
Abstract The formation of facial arteriovenous fistula (AVF) directly between the facial artery and vein after trauma is very rare. Compared with intracranial AVF, understanding of this condition is limited. This paper reported the case of a 49-year-old male who had a metallic foreign object impaled on his left neck while weeding 6 months prior to admission. However, 3 months prior to admission, he developed a gradual throbbing of the left neck and swelling on the left side of his face. Auscultation revealed a vascular murmur in front of the mandibular angle on the left side of the face. Digital subtraction angiography (DSA) showed an AVF between the left lateral facial artery and vein, resulting in retrograde blood flow into cavernous sinus though the ophthalmic vein. The authors discuss the management of a traumatic AVF through combined transarterial embolization using coils and Onyx liquid embolic agent. A 3-month follow-up indicated no recurrence of AVF, and the patient had a great recovery with normal-appearing left face and eye. It was the isolated involvement of the facial artery and vein in a post-traumatic setting makes this case particularly instructive. In addition, we summarized the clinical symptoms and treatment of AVF in the face and neck regions.